Learning from West African Experiences in Security Sector Governance - Bryden, Alan; Chappuis, Fairlie (Ubiquity Press, 2015)
"Many efforts have been undertaken to address dysfunctional security sector governance in West Africa. However, security sector reform (SSR) has fallen short of radical - transformational - change to the fundamental structures of power and governance in the region. Looking more closely at specific examples of SSR in six West African countries, Learning from West African Experiences in Security Sector Governance explores both progress and reversals in efforts by national stakeholders and their international partners to positively influence security sector governance dynamics. Written by eminent national experts based on their personal experiences of these reform contexts, this study offers new insights and practical lessons that should inform processes to improve democratic security sector governance in West Africa and beyond. "This volume has markedly moved the ball forward in the continuous efforts to better understand SSR experiments, specifically in West Africa. Through what could be dubbed 'street level analysis of SSR' (their concept of "micro-dynamics of SSR"), the editors have introduced a perceptive and innovative vista through which to examine and take stock of SSR processes. A must read volume for academics and practitioners of SSR alike in order to integrate the lessons and add to their knowledge base the valuable insights contained in the various chapters." - Dr. Boubacar N'Diaye, Executive Committee Chair, African Security Sector Network (ASSN); Professor of Political Science and Pan-African Studies, The College of Wooster, USA A French translation of this book can be viewed, for free, at: http://dx.doi.org/10.5334/bav"